Perbandingan Densitas Pencarian Internet Untuk Teknologi Terbaru Berdasarkan Data Google Trends - Buulolo, Santi Trimurni; Zega, Agusniaman; Zendrato, Sinar Elsa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This research aims to conduct a comprehensive comparative analysis of internet search densities for emerging technologies using Google Trends data. By examining search patterns across multiple cutting-edge technological domains, we explore the relative public interest and digital engagement with innovative technological developments. The study analyzes search trends for technologies such as artificial intelligence, quantum computing, blockchain, augmented reality, and renewable energy technologies between 2019 and 2024. Utilizing advanced data mining and statistical analysis techniques, we extract meaningful insights into technological awareness, global interest patterns, and potential correlations between search densities and technological advancement. The research methodology involves systematic data collection from Google Trends, comprehensive statistical processing, and in-depth comparative analysis. Results reveal significant variations in search densities across different technological domains, highlighting emerging technological landscapes and potential future innovation trajectories.